THE USE OF ARTIFICIAL INTELLIGENCE-BASED CHAT-GPT AND ITS CHALLENGES FOR THE WORLD OF EDUCATION; FROM THE VIEWPOINT OF THE DEVELOPMENT OF CREATIVE WRITING SKILLS - Shidiq, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Artificial Intelligence is a system with the same intelligence as humans and is characterized by the ability to learn, adapt, solve problems, make decisions, and understand human language. Artificial Intelligence provides many conveniences in the world of education, such as using several systems such as virtual mentors, voice assistants, innovative content, smart classrooms, automatic assessment, and personalized learning. However, on the other hand, there is the ChatGPT system, an AI-based chatbot with the ability to produce text in various formats—whether formal, informal, or creative writing—that poses challenges in the world of education. The ease of ChatGPT in processing information from text input reduces the originality of work, so it tends to be uncreative. The ability of the Chat-GPT system to understand human language makes it very easy to write creatively, such as writing poems, short stories, novels, or other types of writing whose quality is equivalent to human work. Using the study of creative writing theory, this article aims to discuss the ChatGPT system and its impact on students' lack of creativity in writing skills. This article uses qualitative methods with library research data collection techniques by analyzing scientific journals and other articles relevant to the discussion.